Islamic Political Ethics as a Framework for National Security and Good Governance in Contemporary States - Muhammad Muhammad; Bello Ali; Aminu Sa’ad Abdullahi (Walidem Institute and Publishing (WIP), 2026)
Objective: This study aims to analyze the relationship between Islamic political ethics, national security, and good governance based on the Qur'an, Sunnah, and the thought of scholars, as a normative framework to answer the challenges of modern governance. Theoretical framework: The theoretical framework is based on the principles of Tawḥīd, Risālah, and Khilāfah, which are realized through justice, deliberation, accountability, rule of law, benefit, and ethical leadership as the foundation of governance. Literature review: A literature review integrates literature on Islamic political ethics, good governance, and national security from primary Islamic sources as well as classical and contemporary scholarly works to explain the relevance of Islamic values in modern governance. Methods: The research uses a qualitative approach with a doctrinal research design through documentary analysis of the Qur'an, Sunnah, and scientific literature on political ethics, governance, and national security. Results: The results show that the principles of Islamic political ethics strengthen institutional legitimacy, transparency, accountability, national security, and sustainable development, while complementing the concept of modern governance. Implications: The integration of Islamic political ethics in the modern system of governance has the potential to improve the quality of governance, strengthen national security, build public trust, and promote sustainable political stability. Novelty: The novelty of this research lies in the conceptual integration of Islamic political ethics, national security, and good governance in one comprehensive normative framework for contemporary governance.